Halliwell's filmgoer's and video viewer's companion (HarperCollins, 1988)
The book contains thousands of entries providing a wealth of information on American, British, and European actors, directors, and writers, as well as synopses of major films and definitions of terms used in the film industry. It's all here: personal data on actors past and present, including their real names; Academy Award winners and nominees; dates when films were completed and first shown; titles of films as they are known in their country of origin; complete filmographies for many actors